ҚАРАҚАЛПАҚ ТИЛИНДЕ КИЙИМ-КЕНШЕК АТАМАЛАРЫНЫҢ АЙЫРЫМ МӘСЕЛЕЛЕРИ - Зайрова, Қ. (FAN va JAMIYAT, 2018)
The article is devoted to the study of the names of clothes in the Karakalpak language. They are divided into two groups: proper Karakalpak words and borrowed words.